Television and Attention Problems - Diana Converse (EDIS)
“Many parents at one time or another have put a young child in front of a television for a few minutes of household peace. Making a routine of this, however, may create long-term problems.” This 2-page Family Album Radio transcript was written by Diana Converse and published by the UF Department of Family Youth and Community Sciences, July 2012.